A new superimposed model of the Tongnanba anticline in northeastern Sichuan and its exploration implications - Zhai, Yonghe; Chen, Zhuxin; Zhang, Yuqing; Su, Nan; Wang, Lining; Ren, Rong; Yang, Geng (Frontiers in Earth Science, 2023)
Understanding the structural style, kinematic process, and timing of superimposed structures is crucial for regional tectonic evolution analysis and hydrocarbon exploration. The Tongnanba anticline in the oil-and-gas-bearing northeastern Sichuan Basin was subjected to the compression of the Micangshan and Dabashan thrust belts, forming a complex multi-stage, multi-directional, and multi-level superimposed structure. By combining geological and seismic data from the Tongnanba region, we evaluated its structural style and deformation sequence, which allowed us to propose a novel kinematic model for the northeastern Sichuan Basin. Our study suggests that the Tongnanba anticline was controlled by three detachment layers, which led to the multi-level detachment thrust structure style displayed as vertical stacking of three deformation layers. Specifically, the upper and middle deformation layers were mainly controlled by South Dabashan thrust belt in the early stage. These deformation layers extended in the NW-SE direction and formed the long-distance detachment thrust structure, which propagated toward the upper and middle detachment layers and was distinguished by a series of pop-up structures. On the other hand, the lower deformation layer was primarily controlled by the Micangshan thrust belt in the late stage. This deformation layer extended in the NE-SW direction and was governed by basement faults with trishear fault-propagation folding mechanism. This lower deformation layer reworked the upper and middle ones’ process is contrary to the current model of superimposed structure for the Tongnanba anticline, which suggested the Dabashan thrust belt dominated upper and middle deformation layer later than the Micangshan thrust belt dominated lower deformation layer. Such a structure-superimposed model provides a new direction for deep/ultra-deep hydrocarbon exploration in the northeastern Sichuan Basin.